Systematics of Indobaetis Müller-Liebenau & Morihara 1982, and related implications for some other Baetidae genera (Ephemeroptera) - Kluge, Nikita J.; Novikova, Eugenia A. (Zootaxa, 2014)
Imagoes, subimagoes and eggs of Indobaetis costai Müller-Liebenau & Morihara 1982 are described for the first time; additional larval characters of I. costai and I. starmuehlneri Müller-Liebenau & Morihara 1982 are reported. A new species Indobaetis microfolius sp.n. is described based on larvae, a male subimago reared from larva and a female subimago extracted from a mature larva. Baetis michaelohubbardi (Selva-kumar et al. 2012) comb.n. is proposed for a species originally attributed to Indobaetis, based on the presence of hind protoptera, three maxillary dentisetae and other characteristics. Newly discovered diversity within the holophyletic taxon Indobaetis disproves a formerly erected idea about the close relationship of Indobaetis and the muticus-group. Thus, the senior genus-group name for the holophylum including the muticus-group is Takobia/g1; in rank-based nomenclature the names Alainites Waltz & McCafferty (in Waltz et al.) 1994 and Acerbaetis Kang & Yang (in Kang et al.) 1994 should be junior synonyms of Takobia Novikova & Kluge 1987 (new synonymy). The Neotropical taxon Caribaetis Kluge 1992 is accepted as genus (stat.n.), rather than a synonym of Fallceon, based on the original diagnosis of the subgenus Caribaetis and taking into account the significance of such character as presence of a posterior seta on the claw, shared with Indobaetis, Baetodes and some other taxa; resultant new combinations are proposed: Caribaetis planifrons (Kluge 1992) comb.n., Caribaetis alcarrazae (Kluge 1992) comb.n. and Caribaetis grandis (Gonzalez-Lazo & Salles 2007) comb.n. A new species synonymy in Fallceon is proposed, based on the presence of a hind wing costal hook in both species: Fallceon poeyi (Eaton 1995) = F. nikitai McCafferty & Lugo-Ortiz 1994 syn.n.